Government Policies and Foreign Direct Investment: Driving Sustainable Economic Growth and Development - Sitepu, Karolina; Tampubolon, Anggiat Martua (IHSA Institute, 2024)
This research examines the impact of government policies on foreign investment, focusing on their effectiveness in fostering sustainable economic growth and development. Through a comprehensive review of existing literature and empirical analysis, the study explores key policy instruments such as fiscal incentives, regulatory reforms, and sector-specific strategies. The findings highlight that well-designed policies can significantly enhance a country's attractiveness to foreign investors by reducing investment risks, improving infrastructure, and promoting technological innovation. However, persistent challenges such as political instability, corruption, inadequate infrastructure, and regulatory complexities continue to pose barriers to effective policy implementation. Case studies and comparative analyses illustrate successful policy interventions in countries like Singapore and South Korea, where strategic investments in education, infrastructure, and innovation have driven economic transformation. These examples underscore the importance of policy coherence, institutional capacity building, and international cooperation in optimizing the benefits of foreign direct investment (FDI). The research concludes with implications for policymakers to prioritize governance reforms, enhance transparency, and foster inclusive growth strategies that harness the potential of FDI for sustainable development.